Search for diphoton events with large missing transverse momentum in 7 TeV proton-proton collision data with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2012)
A search for diphoton events with large missing transverse momentum has been performed using proton-proton collision data at s=7 TeV recorded with the ATLAS detector, corresponding to an integrated luminosity of 4.8 fb-1. No excess of events was observed above the Standard Model prediction and model-dependent 95% confidence level exclusion limits are set. In the context of a generalised model of gauge-mediated supersymmetry breaking with a bino-like lightest neutralino of mass above 50 GeV, gluinos (squarks) below 1.07 TeV (0.87 TeV) are excluded, while a breaking scale Λ below 196 TeV is excluded for a minimal model of gauge-mediated supersymmetry breaking. For a specific model with one universal extra dimension, compactification scales 1/R<1.40 TeV are excluded. These limits provide the most stringent tests of these models to date. © 2012 CERN.